Posterior reversible encephalopathy syndrome (PRES): Is DWI a prognosis factor?. (February 2020) - Marrone, Luiz Carlos Porcello; Martins, William Alves; Ramos, Sirlei Westernower Monteiro Iranso; Tomasi, Gustavo Henrique; Garcia, Márcio Severo; Marrone, Bianca Fontana; Gadonski, Giovani; Poli-de-Figueiredo, Carlos Eduardo; da Costa, Bartira Ercilia Pinheiro; Soder, Ricardo Bernardi; Huf Marrone, Antônio Carlos; da Costa, Jaderson Costa
Highlights: Discuss the potential use of DWI as a prognosis data in this PRES. Presents a data bank with 70 cases of PRES. (the majority of literature in this diseases is based in case reports). Descibe clinical differences between restricted and normal DWI patients. Abstract: Introduction: Posterior reversible encephalopathy syndrome is a clinicoradiologic entity with typical MR imaging showing a white matter vasogenic edema predominantly affecting the occipital and parietal lobes of the brain. The aim of this article is evaluated the importance of DWI as a prognosis factor in patients with PRES. Materials and methods: We reviewed data from 70 patients with PRES (35 with restricted DWI and 35 with no DWI abnormalities), that were admitted to Hospital São Lucas-PUCRS. These two groups were evaluated in age, sex, previous diseases and past medical history, use of medications, the neurologic manifestations, the highest blood pressure during the neurologic presentation and the highest creatinine during the period of observation. Results: Evaluating 70 patients with PRES with a mean age of 25.4 years old (range from 2 to 74 years old; 55 female and 15 male) we identified 35 cases were brain MRI presents with restricted DWI. Restricted DWI was associated with higher mortality in 90 days (14.2% vs 0.0%; p: 0.027). Conclusions: Few articles present new data that will help clinicians in therapeutic decisions or that modify the knowledge of this syndrome. We suggested that restricted DWI is associated with a worst prognosis in PRES.